ANALISIS KAJIAN POTENSI PROSPEK USAHA JAJANAN MALAM HARIDI KOTA MEDAN - Saragih, Nawary (UNIKA Santo Thomas, 2015)
The purpose of this study was to: (1). Describe the main attraction of tourism potential prospects night snacks in Medan. (2). Examines the characteristics of tourists who visit the centers of business prospects night snacks Medan. (3). Assessing the behavior patterns of tourists visiting in the centers of business prospects night snacks Medan. (4). Assessing the perception of tourists to the potential business prospects night snacks in Medan. In order for the city of Medan can become a tourist destination evening snack can be achieved, the necessary development strategies: (1) .Menjaga and create the taste of food and beverages, for example Typical City of Medan. (2). Improve comfort and security of tourists in the centers of the evening snacks. (3). Maintain and enhance the overall area of cleanliness in the centers of the evening snacks. (4). Improve and maintain the appearance of employees in serving tourists. (5). Prices of food and beverages made cheap but the quality is maintained. To take advantage of the vast opportunities, the local government of Medan city are expected to participate more intensively to support the development of snacks in the evening in the city of Medan. The existence of policies and extension is considered to be very helpful in the completion of cooking the evening snacks. In addition, local governments also need to facilitate the growth and development of tourism products industry night snacks with supporters as hardwares local regulations that can accommodate the interests of employers / principals hari.Terkait evening snacks of local government funding can also be a bridge to help the funding recommendation to the entrepreneur evening snacks through cooperatives and banks, one of which is a government-owned bank, Bank of North Sumatra.